Prosedur Pengurusan Pergantian Bendera MV. Atlas Link Menjadi Bendera Indonesia di Kantor Syahbandar Belawan oleh PT. Multi Jaya Samudera Cabang Belawan - Kevin Pratama Sodipta Banci; Dirhamsyah Dirhamsyah; Yuna Sutria (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This paper discusses the MV Flag Change Procedure. Atlas Link becomes the Indonesian flag at the Harbor Master's Office. This process aims to understand the steps from submitting an application to issuing an approval letter, as well as registration at the Directorate General of Sea Transportation. This research also identified various required documents, including bills of sale, certificates of fitness, and safety documents. In addition, this paper describes the role of the harbormaster in ensuring compliance with maritime regulations and international standards, as well as the challenges faced during the document validation process with the country of origin. In writing this paper the author used field research and library research methods, and the conclusion that can be drawn is that the procedure for changing the MV Atlas Link flag from a foreign flag to an Indonesian flag at the Belawan harbormaster's office, Medan, involves several important steps, including submitting an application, checking documents. , ship inspection, validation with the country of origin, and registration at the Directorate General of Sea Transportation. During this process the harbormaster acts as an authority who ensures that all steps are carried out in accordance with applicable maritime regulations, both at the national and international level. Compliance with international standards, such as those set by the IMO, is also essential to maintain shipping safety and environmental protection, although these procedures are self-explanatory, obstacles such as difficulties in communication with the country of origin and validation of documents can affect the smoothness of the process. Therefore, proper supervision and handling is very necessary to prevent legal problems and ensure safe ship operations.